2003
DOI: 10.1021/ja029740t
|View full text |Cite
|
Sign up to set email alerts
|

Bis(calix[4]diquinone) Receptors:  Cesium- and Rubidium-Selective Redox-Active Ionophores

Abstract: A new class of redox-active ionophore comprised of two calix[4]diquinone moieties connected through either alkylene or pyridylene linkages has been developed. Spectroscopic and electrochemical investigations, X-ray crystal structure analyses, and molecular modeling studies show butylene- and propylene-linked members of this family of redox-active receptors exhibit remarkable selectivity preferences and substantial electrochemical recognition effects toward cesium and rubidium cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Further oxidation of 13 gave anthraquinone 14 and the rearranged imidazolyl oxanthrone 15 as final products.F e 3 + -mediated oxidation of compound 1 led to the efficient preparation of dibenzoquinone skeleton 16,whichwas previously obtained either by thallium trifluoroacetate mediatedo xidation [18] or by chlorine dioxide oxidation. [19] Because calix [4]quinone derivatives are useful intermediates for furtherm odification to alkaline earth selective ionophores, [16,[18][19][20] Fe 3 + -mediated oxidation provides am ild and convenient methodf or their preparation and future applications. Using ag reater excess of Fe 3 + to react with compound 1,w ef ound further oxidation of the 3-(9-anthryl)-1,2,4-oxadiazolyl groups into mono-(17)a nd bis-oxanthrones 18.A ll structures were confirmed by spectrald ata and key products 13-15 from the oxidation of 4 by Fe 3 + were further confirmed by X-ray singlecrystal structurala nalyses.…”
Section: Resultsmentioning
confidence: 99%
“…Further oxidation of 13 gave anthraquinone 14 and the rearranged imidazolyl oxanthrone 15 as final products.F e 3 + -mediated oxidation of compound 1 led to the efficient preparation of dibenzoquinone skeleton 16,whichwas previously obtained either by thallium trifluoroacetate mediatedo xidation [18] or by chlorine dioxide oxidation. [19] Because calix [4]quinone derivatives are useful intermediates for furtherm odification to alkaline earth selective ionophores, [16,[18][19][20] Fe 3 + -mediated oxidation provides am ild and convenient methodf or their preparation and future applications. Using ag reater excess of Fe 3 + to react with compound 1,w ef ound further oxidation of the 3-(9-anthryl)-1,2,4-oxadiazolyl groups into mono-(17)a nd bis-oxanthrones 18.A ll structures were confirmed by spectrald ata and key products 13-15 from the oxidation of 4 by Fe 3 + were further confirmed by X-ray singlecrystal structurala nalyses.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 For example, biscalixarenes joined via tail-to-tail linkage provide two diverging cavities and have been utilized for the formation of polycaps, 6 as redoxactive ionophores 7 and ditopic receptors 8 etc. Earlier, our research group members have demonstrated the synthesis 9,10 and application [11][12][13][14][15][16] of various calixarenes as hosts in selective complexation with different guests such as cesium ion, 11,12 fullerenes [13][14][15] as well as in transportation of uranyl ion across a liquid membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades calixarene macrocycles have found a wealth of applications in several fields related to supramolecular chemistry, [1] which include, for example, cation, [2] anion, [3] or molecular [4] receptors, chemosensors, [5] self-assembling systems, [6] mechanically interlocked molecules, [7] and nanoporous materials. [8] Among all these applications, their use in catalysis, proposed by Gutsche since his pioneering works, [9] still remains relatively limited and "continues to pose an interesting intellectual and synthetic challenge to organic chemists".…”
Section: Introductionmentioning
confidence: 99%